Potential Role of Dexa Scan in Predicting Osteoporosis Risk in Epileptic Patients - Pardeep Mandhan, Jaysingh, Qamar Un Nisa, Saira Abbas, Wajid Jawaid, Mujeeb-Ul-Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Abnormalities of bone health are common among epileptic patients. A Dual-energy x-ray absorptiometry (DEXA) scan is the gold standard for diagnosing osteoporosis and low bone mass. Material and Methods: The design of this study was across-sectional study. This study was carried out from 8th March 2019 to 7th September 2019 in the Department of Neurology, Jinnah Postgraduate Medical Centre, Karachi. We included a total of 400 patients. The diagnosis and classification of epilepsy were according to history, neurological examination, electroencephalography, and neuroimaging (CT or MRI). All the patient sunders went a DEXA scan to calculate T-score, Z-score, and Bone mineral density. Descriptive statistics were calculated. Stratification was done using the student t-test, and P value ≤ 0.05 was taken as significant. Results: There were 66.3% male and 33.8% female patients. Total 62% cases had chronic, and 38% had acute epilepsy. Mean T-Score and Z-score were -1.15±0.53 and -1.04±0.46, respectively. The results showed significant mean difference of T and Zs core among the status group (P=0.000). Thus, there were significant mean differences of T-score and z-Score (P=0.040). Practical implication : The aim of this work is to evaluate bone mineral density (BMD) in patients with idiopathic epilepsy under anti-epileptic drugs and to determine the effect of the type and the duration of drug administration on BMD. Conclusion: The T-score and Z-score of the DEXA scan showed that abnormalities of bone health are common among epileptic patients. Keywords: Bone Mineral Density, Epilepsy, Dual Energy X-Ray Absorptiometry Scanner,